Correlates of COVID-19 vaccine uptake among the forcibly displaced: evidence from Libya - Meshack Achore (BMC, 2024)
Abstract Background Vaccine hesitancy and refusal can hinder the control of infectious diseases such as coronavirus disease 2019 (COVID-19). Although forcibly displaced individuals are at high risk of contracting COVID-19, evidence shows that they are less likely to accept the COVID-19 vaccine. Given their predicament, the factors influencing vaccine uptake in the general population might differ vastly from those in displaced populations. Given the limited evidence on vaccine uptake from humanitarian settings, the current study examined the determinants of COVID-19 vaccine uptake among the forcibly displaced in Libya. Methods Data were extracted from the World Bank/United Nations High Commissioner for Refugees (UNHCR) microdata repository. Data were collected between April and July 2021 after the rollout of the first dose of the COVID-19 vaccine in Libya. Percentages, means, and standard deviations were used to quantify the distribution of the sample population. Logistic regression models were employed to identify factors influencing COVID-19 vaccine uptake. Results Odds ratios (ORs) with p values are used to present the regression analysis results. The study revealed that people unaffected by COVID-19 were less likely (OR = .71, 95%CI = 0.67-0.89) to accept the vaccine. Similarly, individuals with access to free COVID-19 vaccines were more likely to be vaccinated than those without free vaccines (OR = 38, 95%CI = 0.19-0.28). Finally, the results indicated that individuals were six times more likely to be vaccinated at mass vaccination sites ((OR = 6.31, 95%CI = 5.46- 7.94) and 1.92 times more likely to be vaccinated at local health centers (OR = 1.92, 95%CI = 0.1.72-3.11) than they were at hospitals and distant health facilities. Conclusion Implementing comprehensive mass vaccination venues, public education initiatives, and awareness campaigns regarding the importance of vaccination can decrease vaccine hesitancy among the forcibly displaced.